NavMol 3.0 - Binev, Yuri (2019)
This work was supported by the Calouste Gulbenkian Foundation [Programme 'Qualifying New Generations 'grant number 137831], Associated Laboratory for Sustainable Chemistry-Clean Processes and Technologies-LAQV which is financed by Portuguese national funds from Fundacao para a Ciencia e a Tecnologia/MEC [UID/QUI/50006/2013] and co-financed by the ERDF under the PT2020 Partnership Agreement [POCI-01-0145-FEDER-007265]; and NOVA-LINCS [PEest/UID/CEC/04516/2013].